1993
DOI: 10.1007/bf00377710
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the reproducibility of strength and endurance handgrip parameters using a digital analyser

Abstract: A group of 40 healthy individuals (27 women and 13 men) participated in a handgrip test and were retested 1-2 months later. A strain-gauge sensor with a digitised signal and computerized printout was used. A 5-s maximal squeeze test was first made three times, followed by one endurance test with 45%-55% power of the maximal value. The best maximal value was most often (42%) achieved in the third (initial test) or second (retest) attempt. The reproducibility of maximal value was very good; the Pearson correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 9 publications
1
38
0
Order By: Relevance
“…Until now, many researchers [5,7,14,15,20] have suggested that the rising force phase of the force-time curve in explosive isometric contraction can evaluate different muscle functions from maximal strength, explosive strength (power) or muscle contraction speed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, many researchers [5,7,14,15,20] have suggested that the rising force phase of the force-time curve in explosive isometric contraction can evaluate different muscle functions from maximal strength, explosive strength (power) or muscle contraction speed.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the rising force phase (the initial phase until reaching the peak force) in force-time curves during explosive isometric contraction has revealed the existence of individual differences and gender differences [6][7][8][9][10][11][12][13][14]. Walamies and Turjanmaa evaluated the integrated area until the peak strength (impulse) during explosive isometric grip as a 'power factor' with a similar concept to muscle power [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the grip was set so that the subject easily controlled the grip. The test of controlled force exertion was similar to a commonly used test of grip strength (Walamies and Turjanmaa, 1993;Skelton et al, 1994), except for the exertion of prolonged submaximal grip. The subject stood upright with the wrist in the neutral position between flexion and extension and the elbow extended and close to the body and then exerted the grip.…”
Section: Test and Test Proceduresmentioning
confidence: 99%
“…Static muscle endurance has, generally, been evaluated by sustained isometric or intermittent repeated muscle contraction using relative intensity based on each individual's maximal strength [3][4][5][6][7]. In the case of sustained isometric contractions above 50% MVC, the force output decreases markedly in the initial phase and reaches an almost steady state at 15-20% MVC within 150-180 s [4,[6][7][8][9] With intermittent repeated muscle contractions, the force output is largely influenced by an exertion interval as well as sustained time [10] because of repeated muscle contraction and relaxation.…”
Section: Introductionmentioning
confidence: 99%